2023
DOI: 10.1111/nph.18897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen deposition on carbon and nutrient cycling along a natural soil acidity gradient as revealed by metagenomics

Abstract: Nitrogen (N) deposition and soil acidification are environmental challenges affecting ecosystem functioning, health, and biodiversity, but their effects on functional genes are poorly understood.Here, we utilized metabarcoding and metagenomics to investigate the responses of soil functional genes to N deposition along a natural soil pH gradient. Soil N content was uncorrelated with pH, enabling us to investigate their effects separately.Soil acidity strongly and negatively affected the relative abundances of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 112 publications
(148 reference statements)
1
2
0
Order By: Relevance
“…Soil microbes influence soil nutrient cycling, decomposition processes and plant health by modifying their metabolic functions [52]. In the present study, pathways related to cell metabolism and genetic information processing appeared significantly increased under salt stress in both salt-sensitive and salt-tolerant varieties of soybean (Figure 8A).…”
Section: Discussionsupporting
confidence: 53%
“…Soil microbes influence soil nutrient cycling, decomposition processes and plant health by modifying their metabolic functions [52]. In the present study, pathways related to cell metabolism and genetic information processing appeared significantly increased under salt stress in both salt-sensitive and salt-tolerant varieties of soybean (Figure 8A).…”
Section: Discussionsupporting
confidence: 53%
“…It also relates to microorganisms producing these compounds, which are significantly enriched in various ecological niches. Soil physicochemical properties are the most important environmental factors affecting microbial and functional gene composition (Jiang et al, 2021;Hagh-Doust et al, 2023). We found that fungal communities were more sensitive to ginseng cultivation years and soil physicochemical properties relative to bacteria (Table 1 and Figure 7).…”
Section: Figurementioning
confidence: 89%
“…Atmospheric N deposition leads to N enrichment in soil, inducing changes in plant growth and soil biological activity, thereby affecting global carbon (C) and N cycling (Püspök et al, 2023 ). Nitrogen deposition affects soil C cycle functional genes more than N cycle functional genes (Li et al, 2022b ; Hagh-Doust et al, 2023 ). It is reported that N deposition increased the relative abundance of genes related to labile C degradation, on the contrary, the relative abundance of functional genes related to degradation of more recalcitrant C did not change or decrease (Ma et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%